Contentious-administrative appeal, second instance and effective protection (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2024)
The aim of this paper is to analyse the regulation of the contentious-administrative appeal and its interpretation and application by the national courts and the European Court of Human Rights from the perspective of the rights and guarantees of citizens relating to a fair trial.
Keywords: Contentious-Administrative Appeal; Fundamental rights; procedural guarantees